Evaluation of middle ear pressure and post-operative adenoid size in adenotonsillectomy: comparison between curettage and endoscopic assisted coblation technique - Bhat, Sweekritha N.; Dutta, Angshuman (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The aim of the study is to evaluate the effect on middle ear pressure and study the residual adenoid size post adenotonsillectomy after adenotonsillectomy by curettage and endoscopic assisted coblation among pediatric age group. Methods: The present study was designed as a prospective observational study among patients undergoing adenotonsillectomy in a tertiary care hospital among pediatric age group (7-13 years) by measuring middle ear pressure (by tympanometry) and residual adenoids post adenoidectomy by diagnostic nasal endoscopy in 60 patients. The patients were included by simple random sampling, 30 patients for each group one undergoing cold steel the other endoscopic coblation adenotonsillectomy. Results: Greater reduction was observed in the post-operative adenoid size with endoscopic assisted coblation as compared to curettage. The difference in the middle ear pressure at pre operatively, day 1, day 7 and at 3 months between the study groups was not statistically significant. Conclusions: In our study endoscopic coblation technique was found to be more superior to curettage in terms of greater reduction in adenoid mass. The effects on transient middle ear pressure between both study groups showed no difference.